Analysis of pesticide residues in tea using accelerated solvent extraction with in-cell cleanup and gas chromatography tandem mass spectrometry - Abdul Kadir, Haslina; Abas, Faridah; Zakaria, Osman; Ismail, Intan Safinar; Lajis, Nordin (Royal Society of Chemistry, 2015)
A fast, simple and easily automated method was developed for the simultaneous determination of pesticide residues in tea using accelerated solvent extraction (ASE) with in-cell clean up and gas chromatography-tandem mass spectrometry (GC-MS/MS). This method integrates extraction and clean up processes into a single step, by adding a clean-up sorbent along with the sample into the extraction cell. The efficiency of this method was characterized in terms of its recovery (with values ranging from 90 to 98%), repeatability along with intermediate precision (showing relative standard deviations less than 15%), and sensitivity (providing detection limits between 0.001 and 0.007mgg1). The concentration range of the pesticide residues found in the sample is from 0.008 to 0.161mgg1. The relative expanded uncertainty achieved for this method ranged from 24% to 34%. The results indicate that the proposed method is easy and reliable for the determination of pesticide residues in tea, and it is suitable for use in routine analysis.